Symptoms of Depression in Patients with Chemosensory Disorders - M. Tata Suharta (Open Access Indonesian Journal of Medical Reviews, 2021)
Chemosensors are frequently reported in patients with chemosensory impairment. The present investigation intends to clarify whether there are differential pacts on symptoms of depression between the types (smell dysfunction, taste dysfunction, and combination smell and taste dysfunction), severity, length, or source of dysfunction. At the same time, diminished olfaction input and taste appear to have a detrimental influence on emotional dysfunction aggravation. In patients with mixed olfactory or gustatory dysfunction in clinical practice, early management should be considered for depressure symptoms. The current study sought to compare depressive symptoms in patients with mixed olfactory/gustatory dysfunction, purely olfactory disorder, and gustatory disorder, as well as to investigate the relationships between chemosensory function and depressive symptoms in various groups.